What do we know about the future of agriculture in Argentina, Brazil, Paraguay, and Uruguay? - Jorge, Nicolas; Campos, Silvia Kanadani; Gianatiempo, Juan Pablo; Pereira, Vanessa da Fonseca; Piñeiro, Valeria (International Food Policy Research Institute, 2025)
Argentina, Brazil, Paraguay, and Uruguay (ABPU) have significant weight in the global agricultural market. In 2020–2022, the bloc accounted for 53.1 percent of Latin America and the Caribbean’s total agricultural exports, and 9.3 percent of the world total. This contribution is key in many products at the global level too, such as soybean products (for which the group accounts for 56 percent of world trade), corn (32 percent), bovine meat (26 percent), poultry meat (20 percent), pork meat (6 percent), and wheat (6 percent) (2020–2022 Comtrade data).